SOME ASPECTS OF REPRODUCTIVE EFFICIENCY IN AWASSI EWES: A REVIEW - Alkass, Jalal E.; Hermiz, Hani N.; Baper, Mevan Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Reproductive efficiency in terms of fertility, Prolificacy and survival rate are considered the major components of overall efficiency in sheep productivity. While fertility of Awassi ewes is moderate to high depending on feeding and management practices, however, litter size is low and Awassi is not considered a prolific breed. Heritability estimates of these traits are rather low, and reflect small genetic variation in these traits. The possible avenues for increasing reproductive capacity environmentally and genetically are discussed in the text of this review article.